2016
DOI: 10.4103/1305-7456.184159
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of post-contamination treatments affecting different bonding stages to dentin

Abstract: Objectives:To assess the effect of cleansing treatments following saliva and blood contamination at different bonding stages to dentin.Materials and Methods:Labial surfaces of 168 permanent maxillary central incisors were ground flat exposing superficial dentin. Specimens were divided into: uncontaminated control (A), contamination after etching (B), contamination after adhesive application (C), contamination after adhesive polymerization (D). Groups were further subdivided according to cleansing treatments in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
3
16
0
1
Order By: Relevance
“…The time span during which the contaminant interacts with the dentin surface is of significant importance, as longer contamination time results in lower bond strengths than drying the saliva quickly. [22] This observation was related to evaporation of water and formation of a thick film of glycoprotein on the contaminated surfaces. The duration of contamination varies significantly among studies and it is a factor that should be particularly considered when comparing their findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time span during which the contaminant interacts with the dentin surface is of significant importance, as longer contamination time results in lower bond strengths than drying the saliva quickly. [22] This observation was related to evaporation of water and formation of a thick film of glycoprotein on the contaminated surfaces. The duration of contamination varies significantly among studies and it is a factor that should be particularly considered when comparing their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation suggests that rinsing and air-drying provides a collapsed layer of resin deprived collagen which cannot be effectively penetrated. [22,23] Conversely, several studies concluded that there was no adverse effect on bond strength values of two-step self-etching adhesives when contamination occurred after light-curing. [17,25] This can be possibly explained by the simultaneous demineralization and infiltration achieved by these systems.…”
Section: Discussionmentioning
confidence: 99%
“…The results are in agreement with Furuse et al [35], who reported that the re-etching of a cured adhesive eliminated contaminated residue and removed the adhesive coating. The re-bonding after a re-etching procedure assists in the refurbishing of patent adhesives for bonding [8].…”
Section: Discussionmentioning
confidence: 99%
“…Dias Damé JL [7] concluded that water rinsing is a reliable procedure for cavity decontamination. Dina Elkassas et al [8] recommended re-etching rebonding of the affected dentin surface while Juneja R et al [9] suggested the application of NaOCl for the recovery of the bonding potential on the contaminated tooth surface. Few researchers suggest resurfacing with a rotary instrument, followed by water irrigation and reapplication of an adhesive system [10].…”
mentioning
confidence: 99%
“…18 On the other hand, if contamination occurs before polymerization, solvents such as acetone can be used as decontaminants because of their ability to remove unpolymerized monomers. 19 However, if contamination occurs after polymerization of the adhesive, the salivary glycoproteins will attach to the previously polymerized adhesive structure, forming a barrier that prevents the copolymerization of the composite resin, thus affecting the quality of adhesion. 20 The main objective of this study is to evaluate the influence of two saliva decontamination protocols on the adhesive strength of a composite resin to dentin at 24 hours and 6 months after the adhesion procedure, according to the following null hypotheses: 1) Saliva contamination followed by decontamination does not influence the bond strength results;…”
Section: Introductionmentioning
confidence: 99%